Application of Lysine-specific Labeling to Detect Transient Interactions Present During Human Lysozyme Amyloid Fibril Formation. Issue 1 (December 2017) - Ahn, Minkoo; Waudby, Christopher; Bernardo-Gancedo, Ana; De Genst, Erwin; Dhulesia, Anne; Salvatella, Xavier; Christodoulou, John; Dobson, Christopher; Kumita, Janet
Abstract Populating transient and partially unfolded species is a crucial step in the formation and accumulation of amyloid fibrils formed from pathogenic variants of human lysozyme linked with a rare but fatal hereditary systemic amyloidosis. The partially unfolded species possess an unstructured β-domain and C-helix with the rest of the α-domain remaining native-like. Here we use paramagnetic relaxation enhancement (PRE) measured by NMR spectroscopy to study the transient intermolecular interactions between such intermediate species. Nitroxide spin labels, introduced specifically at three individual lysine residues, generate distinct PRE profiles, indicating the presence of intermolecular interactions between residues within the unfolded β-domain. This study describes the applicability to PRE NMR measurements of selective lysine labeling, at different sites within a protein, as an alternative to the introduction of spin labels via engineered cysteine residues. These results reveal the importance of the β-sheet region of lysozyme for initiating self-assembly into amyloid fibrils.